2018
DOI: 10.1108/bepam-10-2017-0105
|View full text |Cite
|
Sign up to set email alerts
|

Economic sustainability of green buildings: a comparative analysis of green vs non-green

Abstract: Purpose In Sri Lanka, a limited number of buildings have been certified for incorporation of green features and the reasons are attributed to green building investors who continue to perceive that green buildings are expensive. Further, the green building investors fail to appreciate the subsequent benefits received by those buildings during the operational phase. Therefore, the purpose of this paper is to compare the life cycle cost (LCC) of green certified industrial manufacturing buildings with a similar fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 12 publications
0
23
0
Order By: Relevance
“…The first two cases (#1 and #2) were publicly funded. Hence, the time and sustainability variables were often sacrificed to the benefit of the cost variable [22,25]. Moreover, in such cases, often the time variable appeared to be considered as the least important of the three.…”
Section: First Dependent Variable: Timementioning
confidence: 99%
See 1 more Smart Citation
“…The first two cases (#1 and #2) were publicly funded. Hence, the time and sustainability variables were often sacrificed to the benefit of the cost variable [22,25]. Moreover, in such cases, often the time variable appeared to be considered as the least important of the three.…”
Section: First Dependent Variable: Timementioning
confidence: 99%
“…Notably, in terms of absolute values, the projects that suffered the greatest cost variance were the ones in which the variable "cost" was the most important of the three [22,25]. As already cited above for the time variance, each project owner had a different order of priorities for each of the three dependent variables.…”
mentioning
confidence: 98%
“…In addition, BIM was presented as a major technological improvement on conventional CAD, providing more intelligence and interoperability capabilities [ 152 ]. It was found that there several studies related to BIM integrates with sustainability and green house buildings [ 153 , 154 , 155 , 156 , 157 , 158 ] in developed countries. A recent study conducted by Naji et al [ 159 ] explored the BIM in lower consumption electric power but was limited to questionnaire data and simulation work and provide a platform for future researchers to explore this simulation work in real-time case studies for validation purposes.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Dwaikat and Ali (2016) indicated that the green building construction cost is higher than that of conventional buildings and falls within the range of 0–21%, depending on the type of building such as office, hospital, library, school, laboratory, house and apartment buildings. Similarly, in the context of Sri Lanka, Weerasinghe and Ramachandra (2018) concluded that the construction cost of a green industrial manufacturing building is 37% higher than that of a similar natured conventional building. Contrary to foregoing, Dwaikat and Ali (2016) stated that there is some evidence supporting that a green building costs less than a conventional building, falls up to 4%.…”
Section: Introductionmentioning
confidence: 98%
“…Similarly, in the context of Sri Lanka, Weerasinghe and Ramachandra (2018) concluded that the construction cost of a green industrial manufacturing building is 37% higher than that of a similar natured conventional building. Contrary to foregoing, Dwaikat and Ali (2016) stated that there is some evidence supporting that a green building costs less than a conventional building, falls up to 4%.…”
mentioning
confidence: 99%